An Introduction to Andalusi Hebrew Metrics - Martínez Delgado, José (Semitic Languages and Cultures, 2023)
Throughout the last two centuries, Hebrew metrics was studied by leading linguists and specialists in medieval Hebrew poetry. Nowadays, it has disappeared from the academic discussion such that it is sometimes even difficult to find scansions or the name of the meter in new editions of poems. This book aims to rectify this gap, helping readers to understand the metric structure of this poetry in order to facilitate the work of editing and cataloguing those samples still in manuscript form for future editors. Delgado presents his view of Andalusi Hebrew metrics, as encountered in medieval manuals of Arabic and Hebrew metrics and scattered notes in the works of Andalusi Hebrew philologists. Whilst twentieth-century scholars spoke about the adaptation of Arabic metrics to Hebrew, he instead approaches these compositions by Andalusi Jews (10th-13th c.) as Arabic metrics written in Hebrew, thus emphasising how Hebrew poetry of the Andalusi Jews can help us to understand the general evolution of Arabic strophic poetry, and its experimental evolution, which is quite unlike classical and strophic Arabic poetry. This method respects the Hebrew vowel system, and does not necessitate alteration of word morphology, leaving the guttural letters quiescent (unless required by metrical license); nor does it necessitate guesses about metres that are not in the classical catalogue. Although the author has not found each and every classical metre from Andalusi Hebrew poetry included in this manual, they are all catalogued, either in case someone finds them in future or because they help us to comprehend the metrical structures that are characteristic of strophic poetry. As such, this monograph will be of great interest to scholars of Hebrew metrics.